The Palestinian-Israeli conflict : a very short introduction - Bunton, Martin P. (Oxford : Oxford University Press, 2013)
The conflict between Palestine and Israel is one of the most highly publicized and bitter struggles in history. In this accessible introduction, Martin Bunton clearly explains the history of the problem, reducing it to its very essence - a modern territorial contest between two nations and one geographical territory.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 2, 2013).
Keywords: Arab-Israeli conflict; Jewish-Arab relations